2014
DOI: 10.11648/j.ajls.20140201.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B surface Antigen among the Newly Admitted Students of University of Jos, Nigeria

Abstract: The study was conducted to assess the prevalence of Hepatitis B surface antigen (HBsAg) among the newly admitted students of University of Jos, Jos Nigeria. A total of 300 newly admitted students were screened using rapid test (Global Rapid Diagnostic Kits USA) for the detection of HBsAg in serum samples from July 2010 to October 2010. The results obtained showed that 50(16.7%) were seropositive to HBsAg. The prevalence of HBsAg was higher in males 34(11.33%) compared to 16(5.33%) in females. Age specific prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…The results are also consistent with the prevalence study carried out in University of Jos, Nigeria (Ekuma et al, 2014) where males had a significantly higher HBsAg prevalence compared to their female counterparts. The knowledge level among students was significantly higher than that among the non-teaching staff probably due to the source(s) of information they had access to.…”
Section: Discussionsupporting
confidence: 90%
“…The results are also consistent with the prevalence study carried out in University of Jos, Nigeria (Ekuma et al, 2014) where males had a significantly higher HBsAg prevalence compared to their female counterparts. The knowledge level among students was significantly higher than that among the non-teaching staff probably due to the source(s) of information they had access to.…”
Section: Discussionsupporting
confidence: 90%
“…In a similar study carried out on fresh students of University of Jos, they recorded a prevalence of 16.67%. 25 Farmers and applicants contributed 1.8% and 1.7% respectively to the total prevalence. Idleness on the part of the applicants may have made them to indulge in certain activities that predispose them to HBV infection.…”
Section: Discussionmentioning
confidence: 97%
“…Also, a total of 3.8% hepatitis B virus which can be considered as low prevalence recorded among the pregnant women in this study area concurs with the ndings of [17,18] who observed a prevalence of 2.8% and 2.19% in Port Harcourt and Benin city respectively. However [19] reported that when hepatitis B virus seroprevalence is greater than 7% in an adult population in a given location, the location thereby should be classi ed as highly endemic for HBV infection. The low prevalence of hepatitis B recorded is contrary to high endemicity of 12.3% and 13.3% recorded in Niger State [20] and Zaria, Kaduna State [21].…”
Section: Discussionmentioning
confidence: 99%